Landmarks of western art [videorecording (DVD)] : a journey of art history across the ages. Impressionism and post-impressionism - Martin, Tim (Timothy) (Landmarks of Western art., 2006)
This episode also features the work of Van Gogh and Degas, and explores such masterpieces as The Sunflowers, La Grande Jette, and The Dancing Class.